The Jizzakh Uprising and its Historical Significance (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, information is provided about the tsar’s decree of Russian conscription for the rear of the front, related riots in 1916, and the most violent of these riots, the Jizzakh Uprising. The Jizzakh Uprising is a national liberation movement of Jizzakh and its surrounding residents against the colonial rule of Tsarist Russia, and the names of the leaders of the movement and those who actively participated in it have earned a worthy place in the glorious history of our country to this day.